Consciência, consciência de classe e luta política no materialismo histórico de Marx e Engels - Galine, Fernando Tadeu Mondi (2020)
In this research we observed the process of formation and development of conscience, especially of class conscience in workers and its role in the organization and in the political struggle. We will also analyze the party's role in this struggle, according to Historical Materialism. As the class struggle and how, in its development, class consciousness manifests itself. In this sense, the party's function is to organize the class struggle by promoting class consciousness. The class struggle advances, especially in times witch the organic crisis of capitalism is most severe, Marx, in the 1859 Preface to A Contribution to the Critique of Political Economy, calls this intensification a stage of revolution. Analyze class consciousness helps us to understand that it is not something given, but that it requires permanent work, and that in the stages of revolution, class consciousness allows us to advance the end of exploitation of man by man. We also studied the relation between class consciousness and ideology. The dominant ideology, being always the worldview of the class that dominates materially, perform a role in maintaining the status quo. However, with class consciousness for itself, the subordinate class breaks with the dominant ideology, and develops its own worldview, a vision that seeks to end class society and the structure of exploitation of man by man. For this research we will use mainly the books: The German Ideology by Karl Marx and Friedrich Engels, Economic and Philosophic Manuscripts by Marx and The Condition of the Working Class in England by Engels to watch the process of emergence of class consciousness on workers and The Communist Manifesto to show that, as a consequence of the emergence of class conscientiousness, the workers organized themselves for the political fight.